Studies on Physical Characteristics, Mineral Composition and Nutritive Value of Bone Meal and Bone Char Produced from Inedible Cow Bones - Khalil; Reswati; Ferawati; Kurnia, Y.F.; Agustin, F. (Pakistan Journal of Nutrition, 2017)
Background and Objective: Bone meal and bone char produced from inedible cow bones could be an alternative renewable and low-cost dietary Phosphorous (P) source in poultry diets. This study aimed to evaluate the physical characteristics, mineral composition and nutritive value of bone meal and bone char meal produced from inedible cow bones derived from different body parts of the animal. Materials and Methods: A field survey was carried out to collect data on inedible bones taken from 30 slaughtered cows at sites involved in three meat processing steps: Slaughter house, local meat shops and beef offal processors. Samples of inedible bones grouped into three body parts: Head, ribs and legs were collected and processed into bone meal and bone char meal by soaking in lime water and open-air burning, respectively. The nutritive values of the bone meals were also evaluated by mixing 3% bone meal and bone char with a basal diet that was fed to 150 laying quails. Parameters measured included: Inedible bone weight, percentage of meal yield, content of crude ash and minerals (Ca, P, Fe, Zn, Mn and Cu), physical properties and particle size distribution, egg production, egg shell quality, digestibility and tibia bone mass and mineralization. Results: Present study showed that on average inedible bones represented 13.8 kg/animal or 3.4% b.wt., that could be used to produce bone meal. Percentage of meal yield for bone meal (91.4%) was significantly higher (p